Resistant Soil Microbial Communities Show Signs of Increasing Phosphorus Limitation in Two Temperate Forests After Long-Term Nitrogen Addition - Forstner, Stefan J.; Wechselberger, Viktoria; Stecher, Stefan; Müller, Stefanie; Keiblinger, Katharina M.; Wanek, Wolfgang; Schleppi, Patrick; Gundersen, Per; Tatzber, Michael; Gerzabek, Martin H.; Zechmeister-Boltenstern, Sophie (Frontiers in Forests and Global Change, 2019)
Forest soils harbor diverse microbial communities that are responsible for the cycling of elements including carbon (C), nitrogen (N) and phosphorus (P). Conversely, anthropogenic N deposition can negatively feedback on soil microbes and reduce soil organic matter (SOM) decomposition. Mechanistically, this includes reductions of decomposer biomass, especially fungi, and decreases in activities of lignin-modifying enzyme (LMEs). Moreover, N inputs can decrease the C:N imbalance between microbial decomposers and their resources by lowering resource C:N, resulting in slowed microbially-mediated decomposition and larger SOM pools. Here, we studied the long-term impact of N addition on soil microbes and associated decomposition processes along the topsoil profile in two temperate coniferous forests in Switzerland and Denmark. We measured microbial biomass C and N, phospholipid fatty acid (PLFA) biomarkers and potential enzyme activities. In particular, we investigated shifts in community level homeostasis and relative elemental limitation after two decades of N addition. Contrary to prevailing theory, microbial biomass and community composition were remarkably resistant against twenty years of 780 and 1280 kg ha-1 of cumulative N inputs at the Swiss and Danish site, respectively. While N reduced fungal-specific PLFAs and lowered fungi:bacteria ratios in some horizons, it increased the fungi:bacteria ratio in other horizons. We did not find a consistent reduction of lignin-modifying enzymes (LMEs). This questions prevalent theories of responses of lignin decomposition and SOC storage to elevated N inputs. We further showed that microbial communities responded in part non-homeostatically to decreasing resource C:N, likely through adaptations in microbial elemental use efficiencies. In contrast, the expected increased allocation to C- and decreased allocation to N-acquisition enzymes was not found. Microbial investment into P acquisition (acid phosphatase activity) increased in nutrient-poor Podzols (but not in nutrient-rich Gleysols), while enzyme vector analysis showed decreasing C but increasing P limitation of soil microbial communities at both sites. We conclude that simulated N deposition in two independent, long-term experiments led to physiological adaptations of soil microbial communities with implications for tree nutrition and SOC sequestration. However, we expect that microbial adaptations are not endless and may reach a tipping point when ecosystems experience nitrogen saturation.